2019
DOI: 10.1177/0361198119844965
|View full text |Cite
|
Sign up to set email alerts
|

Rules of the Road: Compliance and Defiance among the Different Types of Cyclists

Abstract: Although cycling has become a more attractive option to commuters in many North American cities recently, significant apprehension remains around its safety. Though risks experienced by cyclists are diverse, the idea that they are because of scofflaw cyclists—cyclists who regularly ignore the rules of the road—remains prevalent. Improving cycling safety requires countering this idea, and therefore an understanding of how different cyclists act under the existing rules. Using a survey of 1,329 cyclists in Montr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…City managers and planners should thus work to close the gender and age gaps by making cycling a more inclusive activity for all genders, ages, and abilities. One way to do this is to alleviate safety concerns of new or fearful cyclists through inclusive infrastructure based on intuitive travel trajectories and rules (Chaloux and El-Geneidy 2019). It is important to better understand how women and men interact as cyclists with the infrastructure in place, as the installed infrastructure may favor, or exclude, certain cyclist typologies and demographic groups.…”
Section: Cyclist Typologiesmentioning
confidence: 99%
“…City managers and planners should thus work to close the gender and age gaps by making cycling a more inclusive activity for all genders, ages, and abilities. One way to do this is to alleviate safety concerns of new or fearful cyclists through inclusive infrastructure based on intuitive travel trajectories and rules (Chaloux and El-Geneidy 2019). It is important to better understand how women and men interact as cyclists with the infrastructure in place, as the installed infrastructure may favor, or exclude, certain cyclist typologies and demographic groups.…”
Section: Cyclist Typologiesmentioning
confidence: 99%
“…Nearly all respondents reported breaking a traffic rule regardless of travel mode; the most common reason cyclists did so was for personal safety (Marshall et al, 2017). A study of cyclists in Montreal, Canada, found that only 0.6% of survey respondents consistently followed all traffic laws (Chaloux and El-Geneidy, 2019). Given a set of four hypothetical scenarios, cyclists most often chose to break a traffic rule when they felt it was safer than precisely following the vehicle code.…”
Section: Cycling Safety and Sidewalk Ridingmentioning
confidence: 99%
“…The four-cyclist typology is: no way no how, interested but concerned, enthused and confident, and strong and fearless. Chaloux (2019) [17] generated another cyclist typology and used it to compare reactions to varying road scenarios and rule following by different cyclist types. They found that "[u]niquely defined by their motivations to cycle, fearfulness, confidence, and lawfulness, all six cyclist types were in agreement when breaking the rules.…”
Section: Introduction 1cycling Benefits and Disbenefitsmentioning
confidence: 99%